The urgency of incorporating real-life conversation into IFL learning materials - Nina Amalia Nurichsania; Suci Sundusiah; Ida Widia (Inovasi Kurikulum, 2024)
While authenticity plays a vital role in foreign language learning, a significant disparity exists between classroom-based learning and the practical use of language in real-world contexts. IFL resources often lack authenticity, failing to mirror the genuine language encounters that learners face beyond the classroom. Therefore, this research explores the motivations, needs, and prior learning experiences of IFL learners to emphasize the importance of integrating real-life conversations into IFL learning materials. This descriptive qualitative research gathered data via surveys and semi-structured interviews with ten foreigners. The findings underscored the varied motivations of participants in learning Indonesian, including personal and familial connections, communication requirements during travel, interests in language, and cultural identity. Participants engaged in instructor-led and self-directed learning as endeavors to boost their proficiency. Intriguingly, there was a discrepancy between their learning experiences and needs. Although the provided IFL materials had successfully fulfilled the learners’ needs in formal settings, they fell short of adequately equipping them for real-world interactions in the intended social settings. Hence, it is suggested that authentic, real-life conversation be incorporated into the IFL materials to meet the diverse practical communication needs of IFL learners.   Abstrak Keautentikan memainkan peranan penting dalam pembelajaran bahasa asing, namun pada kenyataannya terdapat kesenjangan yang signifikan antara pembelajaran di kelas dan penggunaan bahasa dalam konteks kehidupan nyata. Sumber belajar Bahasa Indonesia bagi Penutur Asing (BIPA) kerap kali kurang mencerminkan penggunaan bahasa Indonesia sesungguhnya yang dihadapi pemelajar di luar kelas. Oleh karena itu, penelitian ini bertujuan untuk mengeksplorasi motivasi, kebutuhan, dan pengalaman belajar pemelajar untuk menekankan pentingnya pengintegrasian percakapan real-life dalam materi pembelajaran BIPA. Peneliti mengumpulkan data melalui survei dan wawancara semi-terstruktur. Hasil penelitian deskriptif kualitatif ini menyoroti beragam motivasi pemelajar dalam mempelajari bahasa Indonesia, yakni hubungan pribadi dan keluarga, kebutuhan komunikasi saat bepergian, minat terhadap bahasa, serta identitas budaya. Para pemelajar belajar bahasa Indonesia secara formal dengan instruktur dan secara mandiri sebagai usaha untuk meningkatkan kecakapan berbahasa Indonesia mereka. Meskipun begitu, masih ditemukan kesenjangan antara pengalaman belajar dan kebutuhan belajar para pemelajar BIPA. Walaupun materi BIPA yang tersedia sudah mengakomodasi kebutuhan berbahasa pemelajar di konteks formal, materi tersebut belum memadai dalam mempersiapkan pemelajar untuk interaksi autentik dalam konteks sosial yang dibutuhkan. Berdasarkan temuan dalam penelitian ini, disarankan untuk mengintegrasikan percakapan real-life ke dalam materi pembelajaran BIPA guna memenuhi kebutuhan komunikasi praktis pemelajar BIPA yang beragam. Kata Kunci: Materi autentik; materi BIPA; percakapan kehidupan nyata